2022
DOI: 10.1136/archdischild-2021-322851
|View full text |Cite
|
Sign up to set email alerts
|

Extensive use of on-pack promotional claims on commercial baby foods in the UK

Abstract: ObjectiveTo explore and categorise the nature of promotional claims on packaging of commercial baby foods (CBFs).SettingUKMethodologyAn online survey of CBFs (for infants up to 12+ months) in 7 UK supermarkets and Amazon in 2020. On-pack promotions were classified as marketing, composition, health, and nutrient claims using the WHO Nutrient Profile Model draft for infants and young children, and European Union regulation on health and nutrition claims.Main outcome measureDistribution and proportion of claim ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Such claims can be misleading, especially when placed on products with undesirable qualities, such as high total sugar content. Previous research has found that a significantly greater proportion of products with 'no added sugar' claims were classified as having high sugar content as compared to those without such claims (Garcia et al, 2022;Grammatikaki et al, 2021;Koo et al, 2018). The study has some limitations.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Such claims can be misleading, especially when placed on products with undesirable qualities, such as high total sugar content. Previous research has found that a significantly greater proportion of products with 'no added sugar' claims were classified as having high sugar content as compared to those without such claims (Garcia et al, 2022;Grammatikaki et al, 2021;Koo et al, 2018). The study has some limitations.…”
Section: Discussionmentioning
confidence: 87%
“…Thus, decreasing early exposure to salty tasting foods is recommended to reduce salt intake later in life (Lava et al, 2015;Liem, 2017 Claims on CPCF purées/meals labels were widely prevalent, with compositional claims being the most commonly displayed. Extensive use of claims has been also noted on CPCF products available in the United Kingdom (Garcia et al, 2022), Australia (Simmonds et al, 2021) and Taiwan (Koo et al, 2018). Claims tend to emphasize the natural and organic nature of CPCF purées/meals, as well as the absence of artificial additions or other components often considered by consumers as less desirable, such as added sugar and salt.…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate claims were the most common reason for CPCF cereals failing the labelling practices assessment of the adapted NPM for CPCF. Similarly, extensive use of claims has been noted on CPCF products in the UK (Garcia et al, 2022) and inTaiwan (Koo et al, 2018).…”
Section: Micronutrient Content Assessmentmentioning
confidence: 81%
“…Food labels often display misleading names for the ingredients used in their formulations. For example, food names like “spinach, apple, and swede” suggest that a green vegetable is the main ingredient, but fruit is the main ingredient [ 25 , 26 ]. Commercial baby snacks use messages related to self-feeding behaviour, such as “encourages self-feeding” and “ideal finger food” [ 25 ], which promote snacking on highly processed foods [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, food names like “spinach, apple, and swede” suggest that a green vegetable is the main ingredient, but fruit is the main ingredient [ 25 , 26 ]. Commercial baby snacks use messages related to self-feeding behaviour, such as “encourages self-feeding” and “ideal finger food” [ 25 ], which promote snacking on highly processed foods [ 27 ]. Our group and others have reported the extensive and pervasive use of marketing claims on the packaging of commercial baby foods.…”
Section: Introductionmentioning
confidence: 99%